Interprofessional Collaborative Practice: Management of Chronic Disease and Mental Health Issues in Primary Care. (May 2023) - Esperat, M. Christina; Hust, Christie; Song, Huaxin; Garcia, Monica; McMurry, Linda J.
This case study describes the process of implementing and evaluating an interprofessional collaborative practice (IPCP) program for primary care and behavioral health integration focused on chronic disease management. The result was a strong IPCP program in a nurse-led federally qualified health center serving medically underserved populations. The IPCP program at the Larry Combest Community Health and Wellness Center at the Texas Tech University Health Sciences Center spanned >10 years of planning, development, and implementation, supported by demonstration, grants, and cooperative grants from the Health Resources and Services Administration. The program launched 3 projects: a patient navigation program, an IPCP program for chronic disease management, and a program for primary care and behavioral health integration. We established 3 evaluation domains to track the outcomes of the program: TeamSTEPPS education outcomes (Team Strategies and Tools to Enhance Performance and Patient Safety), process/service measures, and patient clinical and behavioral measures. TeamSTEPPS outcomes were evaluated before and after training on a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree). Mean (SD) scores increased significantly in team structure (4.2 [0.9] vs 4.7 [0.5]; P < .001), situation monitoring (4.2 [0.8] vs 4.6 [0.5]; P = .002), and communication (4.1 [0.8] vs 4.5 [0.5]; P = .001). From 2014 to 2020, the rate of depression screening and follow-up improved from 16% to 91%, and the hypertension control rate improved from 50% to 62%. Lessons learned include recognizing partner contributions and the worth of each team member. Our program evolved with the help of networks, champions, and collaborative partners. Program outcomes show the positive impact of a team-based IPCP model on health outcomes among medically underserved populations.